Exercise increases Rho‐kinase activity and insulin signaling in skeletal muscle. Issue 6 (15th January 2018) - Muñoz, Vitor R.; Gaspar, Rafael C.; Kuga, Gabriel K.; da Rocha, Alisson L.; Crisol, Barbara M.; Botezelli, José D.; Baptista, Igor L.; Mekary, Rania A.; da Silva, Adelino S. R.; Cintra, Dennys E.; de Moura, Leandro P.; Ropelle, Eduardo R.; et al.
Abstract : The effects of physical exercise on insulin signaling and glycemic homeostasis are not yet fully understood. Recent findings elucidated the positive role of Rho‐kinase (Rock) in increasing the glucose uptake through insulin receptor substrate‐1 (IRS1) phosphorylation in the skeletal muscle. Here, we explored the effects of short‐term exercise on Rock activity and insulin signaling. Fischer 344 rats (3 months old) were subjected to a short‐term swimming exercise for 2 hr per day for 5 days, with an overload corresponding to 1.5% of body weight. As expected, the exercised group had a reduced glycemia and increased insulin sensitivity. The contents of Rock1, Rock2, and Rock activity were improved in the skeletal muscle of the exercised rats. The contents of RhoA and RhoGEF, which are proteins involved in the Rock metabolism, were also increased in the skeletal muscle after exercise. These changes in the protein contents were accompanied by an increase in the insulin signaling pathway (pIRS1/pPDK/pAkt/pGSK3β/pAS160/GLUT4), Rock activity, and IRS1 phosphorylation at the 632/635 serine residues. On the other hand, when Rock was inhibited with the Y‐27632, the insulin sensitivity in response to exercise was impaired. Based on these findings, we conclude that the short‐term exercise increased both insulin sensitivity and glucose tolerance, through the increased Rock activity and pIRS1 (serine 632/635) mediated by Rock, in the skeletal muscle of Fischer 344 rats. These data represent an exercise‐mediated novel mechanism, suggesting an essential role of Rock activity in the insulin signaling and glucose homeostasis improvement. Abstract : Short‐term physical exercise modulates Rock metabolism in skeletal muscle, and improves whole body glucose homeostasis and insulin sensitivity in rats. ‐ The exercised animals demonstrated increased Rock activity and IRS1 phosphorylation at S632/635 (Rock specific residue), as well as in insulin signaling pathway. ‐ This is the first study evaluating the role of physical exercise on Rock metabolism. Then, new therapeutic strategies to improve glucose homeostasis and prevent insulin resistance can be considered involving Rock protein.